House secrets - Lawson, Michael (New York : Atlantic Monthly Press, 2009)
When Joe DeMarco is asked by the Speaker of the House to probe the apparent accidental death of a reporter who was trailing presidential hopeful Senator Paul Morelli, dirty secrets and divided loyalties threaten his investigation.
Keywords: Government investigators -- United States; Legislators; Political fiction